Biocrust diazotrophs and bacteria rather than fungi are sensitive to chronic low N deposition. (18th July 2022) - Rong, Xiaoying; Zhou, Xiaobing; Li, Xiangzhen; Yao, Minjie; Lu, Yongxing; Xu, Peng; Yin, Benfeng; Li, Yonggang; Aanderud, Zachary T.; Zhang, Yuanming
Abstract: Anthropogenic long‐term nitrogen (N) deposition may dramatically impact biocrusts due to the overarching N limitation of soil biota in deserts. Even low levels of N may reach a critical loading threshold altering biocrust constituents and function. To identify the impact of chronic and continuous low levels of N deposition on biocrusts, we created a realistic gradient mirroring anthropogenic N addition rate (2:1 NH4 + : NO3 − rates: 0.3, 0.5, 1.0, 1.5, 3 g N m −2  yr −1 ) and measured the response of bacteria and fungi within cyanobacterial‐dominated biocrusts over 8 years in a temperate desert, the Gurbantunggut Desert, China. We found that once N deposition reached 1.5 g N m −2  yr −1 biocrust bacterial communities, including diazotrophs, were altered while no such tipping point existed for fungi. Above the threshold, bacterial richness was enhanced, the relative abundance of Chloroflexi, FBP and Gemmatimonadetes was elevated, and diazotrophs shifted from being dominated by Nostocaceae and Scytonemataceae (Cyanobacteria) to free‐living Bradyrhizobiaceae (Alphaproteobacteria). Alternatively, the relative recovery of a few fungal species within the Lecanorales, Pleosporales and Verrucariales became either enriched or diminished due to N deposition. The chronic addition of N resulted in a dense and interconnected bacterial co‐occurrence network that accentuated a functional shift from networks dominated by phototrophic species within the Nostocaceae, Xenococcaceae, Phormidiaceae and Scytonemataceae (Cyanobacteria) to ammonia‐oxidizing species within the Nitrosomonadaceae (Betaproteobacteria) and nitrifying bacteria [i.e. Nitrospiraceae (Nitrospirae)]. Based on structural equation models, the effects of N additions on biocrust constituents were imposed through indirect effects on pH, soil electrical conductivity and ammonium concentrations. In summary, biocrust constituents are generally insensitive to chronic low levels of N depositions until rates reach above 1.5 g N m −2  yr −1 with diazotrophs being the most sensitive biocrust constituents followed by bacteria and finally fungi. Ultimately once the threshold is reached N deposition favours biocrust constituents utilizing inorganic N and other C sources over relying on phototrophic and/or N‐fixing cyanobacteria for C and N.